2014
DOI: 10.1002/pbc.25123
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of platinum‐induced ototoxicity in pediatric patients in Quebec

Abstract: Ototoxicity following chemotherapy with cisplatin or carboplatin is common and can frequently progress after the completion of treatment. Long-term follow-up is strongly recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 33 publications
1
37
1
4
Order By: Relevance
“…The prevalence of hearing loss is hard to compare in different study populations because of differences in diagnostic groups, cancer treatment, and type of auditory grading. In previous studies the prevalence of questionnaire-reported hearing loss in groups at risk of ototoxicity ranged from 16 to 31% [2,4,21], and was even higher when prevalence was assessed by retrospective data collection in medical records (12–90%) [3,2224]. However, previous studies that are similar to ours may have underestimated the prevalence of hearing loss just as our study did for mild and unilateral hearing loss.…”
Section: Discussionsupporting
confidence: 45%
“…The prevalence of hearing loss is hard to compare in different study populations because of differences in diagnostic groups, cancer treatment, and type of auditory grading. In previous studies the prevalence of questionnaire-reported hearing loss in groups at risk of ototoxicity ranged from 16 to 31% [2,4,21], and was even higher when prevalence was assessed by retrospective data collection in medical records (12–90%) [3,2224]. However, previous studies that are similar to ours may have underestimated the prevalence of hearing loss just as our study did for mild and unilateral hearing loss.…”
Section: Discussionsupporting
confidence: 45%
“…To our knowledge, there has been no reported incidence of cisplatin based hearing loss in the head and neck cancer population. Within the pediatric population, there has been report of as much as 30% clinically significant 2 Advances in Otolaryngology hearing loss [10]. In head and neck cancer, chemotherapy is also combined with radiation for advanced tumors which may work synergistically with cisplatin to increase the risk of hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…In patients receiving carboplatin, the incidence of ototoxicity is approximately 7% (Dean et al, 2008; Jehanne et al, 2009). In patients receiving cumulative cisplatin doses of ≤200 mg/m 2 , 200–400 mg/m 2 , and ≥400 mg/m 2 , the incidence increases to 59, 68, and 65%, respectively (Peleva et al, 2014). Moreover, severe nephrotoxicity has not been reported during carboplatin-therapy and reduction of glomerular filtration rate to less than 50% is less frequent than with cisplatin.…”
Section: Managementmentioning
confidence: 99%